BK polyomavirus infection: more than 50 years and still a threat to kidney transplant recipients - Parajuli, Sandesh; Aziz, Fahad; Zhong, Weixiong; Djamali, Arjang (Frontiers in Transplantation, 2024)
BK polyomavirus (BKPyV) is a ubiquitous human polyomavirus and a major infection after kidney transplantation, primarily due to immunosuppression. BKPyV reactivation can manifest as viruria in 30%–40%, viremia in 10%–20%, and BK polyomavirus-associated nephropathy (BKPyVAN) in 1%–10% of recipients. BKPyVAN is an important cause of kidney graft failure. Although the first case of BKPyV was identified in 1971, progress in its management has been limited. Specifically, there is no safe and effective antiviral agent or vaccine to treat or prevent the infection. Even in the current era, the mainstay approach to BKPyV is a reduction in immunosuppression, which is also limited by safety (risk of de novo donor specific antibody and rejection) and efficacy (graft failure). However, recently BKPyV has been getting more attention in the field, and some new treatment strategies including the utilization of viral-specific T-cell therapy are emerging. Given all these challenges, the primary focus of this article is complications associated with BKPyV, as well as strategies to mitigate negative outcomes.